The role of Angiology and Vascular Surgery in the COVID-19 pandemic - Barros, Bernardo Cunha Senra (2020)
The New Coronavirus Epidemic (2019-nCoV), discovered in the city of Wuhan, China, in December 2019, presents mainly with pulmonary pneumonia that is preceded by fever, cough and myalgia. However, as the disease spread globally and the number of hospitalizations increased exponentially, it was noted that most serious patients hospitalized by COVID-19 have laboratory changes worthy of attention, such as lymphopenia, neutrophilia, increased time of prothrombin and increased levels of D-dimer. Due to these changes proving to be crucial for the mortality and morbidity rates in this subset of infected people, several studies focusing on the pathophysiology, mainly hematological, of the disease appear every day. Deepening these studies, several published works have shown SarsCoV-2 infection to the installation of a prothrombotic state in hospitalized patients, which leads to the potential occurrence of thrombotic or arterial events in this cohort. Thus, in order to understand how the departments of Angiology and Vascular Surgery are acting in the context of the COVID-19 pandemic, this work aims to gather studies that reveal from protocols applied in vascular services in the current situation, until to the role of vascular surgeons and angiologists in the clinical and surgical management of patients infected or not, as a way of helping and clarifying this specialty during the context of a pandemic due to the new coranavirus. For the selection of works, the following search criteria were used: “Coronavirus and venous thrombosis”, “Coronavirus and thrombosis”, “COVID-19 and venous thrombosis” and “COVID-19 Coronavirus and thrombosis”.